2016
DOI: 10.1681/asn.2016020184
|View full text |Cite
|
Sign up to set email alerts
|

IgA1 Glycosylation Is Heritable in Healthy Twins

Abstract: IgA nephropathy (IgAN) is the most common form of primary GN and an important cause of kidney failure. Characteristically, patients with IgAN have increased serum levels of undergalactosylated IgA1 (gd-IgA1). To assess the degree to which serum gd-IgA1 levels are genetically determined in healthy individuals, we determined serum IgA and gd-IgA1 levels by ELISA in a sample of 148 healthy female twins, including 27 monozygotic and 47 dizygotic pairs. Using the classic twin model, we found the heritability of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…In vitro evidence supports a role for these IgA-containing immune complexes in driving glomerular injury through mesangial cell proliferation and secretion of cytokines, chemokines, growth factors and extracellular matrix components promoting glomerular inflammation and glomerulosclerosis [20][21][22] . Consistent with previous data, we show that Gd-IgA1 level is a heritable trait [23][24][25][26] and use a genome-wide approach to identify the common genetic factor that influences Gd-IgA1 levels in Caucasian and East Asian populations.…”
Section: Introductionsupporting
confidence: 90%
“…In vitro evidence supports a role for these IgA-containing immune complexes in driving glomerular injury through mesangial cell proliferation and secretion of cytokines, chemokines, growth factors and extracellular matrix components promoting glomerular inflammation and glomerulosclerosis [20][21][22] . Consistent with previous data, we show that Gd-IgA1 level is a heritable trait [23][24][25][26] and use a genome-wide approach to identify the common genetic factor that influences Gd-IgA1 levels in Caucasian and East Asian populations.…”
Section: Introductionsupporting
confidence: 90%
“…The extent of Mesangial Gd-IgA1 deposition and its serum levels was associated with disease progression [14,15]. However, in a recent multicentric study; there was no favorable effect of rituximab on the level of Gd-IgA1 [16]. Moreover, a recent study questioned the role of autoimmunity in the development of aggressive disease in IgAN and indicated that a higher level of Gd-IgA1 is a hereditary predisposition [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that genetic factors play a major role in influencing the composition of circulating IgA1 O ‐glycoforms in serum with heritability of serum IgA1 O‐galactosylation being reported as high as 80% …”
Section: Differences In Pathogenic Pathways In Igan In Different Ethnmentioning
confidence: 96%
“…There is convincing evidence that genetic factors play a major role in influencing the composition of circulating IgA1 O-glycoforms in serum with heritability of serum IgA1 O-galactosylation being reported as high as 80%. [97][98][99][100] Ogalactosylation of the IgA1 hinge region is mediated by a series of complex stepwise co-/post-translational modifications and one of the key enzymes involved is core 1 beta 1, 3-galactosyltransferase(C1GalT1), whose activity catalyses the addition of galactose to N-acetylgalactosamine. In a recent quantitative trait GWAS multiple single nucleotide polymorphisms (SNP) were identified in the non-coding region of the C1GALT1 gene to be associated with the extent of serum IgA1 O-galactosylation in IgAN, healthy subjects, membranous nephropathy in Caucasian and Chinese cohorts.…”
Section: Differences In Pathogenic Pathways In Igan In Different Ethnmentioning
confidence: 99%